Dietary habits in a group of patients with multiple sclerosis are similar to those of healthy control subjects - MACHADO, Stella Boreggio; CABRAL, Raquel; MURADE, Nadya; ARES, Nayara Cavalcanti; SCORCINE, Claudio; FRAGOSO, Yara Dadalti (Arquivos de neuro-psiquiatria, 2020)
ABSTRACT Background: Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system. Over time, patients with MS accumulate neurological disabilities. MS typically affects young adults and is associated with an inflammatory profile of cytokines and lymphocytes. If a patient were to consume a potentially inflammatory diet, it is possible that the evolution of MS in that individual would be more aggressive. Objective: To investigate whether patients with MS living in and around the city of Santos, São Paulo, Brazil, had a profile of inflammatory diet. Methods: Patients with MS and healthy control subjects were individually interviewed, and the 24-hour Diet Recall and the Bristol Stool Form Scale were applied. Salt intake was calculated using the WebDiet 2.0 software. Results: There were no remarkable differences in dietary habits between healthy control subjects (n=34) and patients with MS (n=66), except for higher consumption of carbohydrates by patients. Both patients with MS and control subjects had higher protein and lower carbohydrate intake than the World Health Organization’s recommended daily amounts. There was no correlation between food intake and neurological disability in patients with MS. Conclusion: The dietary patterns of patients with MS and healthy controls were similar in the city of Santos, São Paulo, Brazil, and surrounding towns, except for higher intake of carbohydrates by patients. No profile of pro-inflammatory diets was identified among the patients with MS enrolled in this study.